An evaluation of anesthetic fade in motor evoked potential monitoring in spinal deformity surgeries - Ryo Ugawa; Tomoyuki Takigawa; Hiroko Shimomiya; Takuma Ohnishi; Yuri Kurokawa; Yoshiaki Oda; Yasuyuki Shiozaki; Haruo Misawa; Masato Tanaka; Toshifumi Ozaki (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background Intraoperative neuromonitoring using motor evoked potentials (MEP) satisfactorily detects motor tract integrity changes during spinal surgery. However, monitoring is affected by “anesthetic fade,” in which the stimulation threshold increases because the waveform amplitude decreases with the accumulation of propofol. Therefore, the purpose of this study was to clarify the effect of anesthetic fade on transcranial MEPs by investigating the time-dependent changes of amplitude during spinal deformity surgeries. Methods We retrospectively reviewed medical records of 142 spinal deformity patients (66 patients with idiopathic scoliosis, 28 with adult spinal deformities, 19 with neuromuscular scoliosis, 17 with syndromic scoliosis, and 12 with congenital scoliosis). The average age was 28 years (range, 5 to 81 years). MEPs were recorded bilaterally from the abductor digiti minimi (ADM) and abductor hallucis (AH) muscles during spinal deformity surgeries. The Wilcoxon signed-rank test was used to investigate the time-dependent changes of amplitude after propofol infusion to evaluate anesthetic fade effects. Results The average time to baseline from initial propofol infusion was 113 min (range, 45 to 182 min). In the ADM, the amplitude was 52% at 1 h after initial propofol infusion, 102% at 2 h, 105% at 3 h, 101% at 4 h, 86% at 5 h, and 81% at 6 h. Compared to the 2-h time point, MEP decreased significantly by 16% at 5 h (P < 0.0005) and by 21% at 6 h (P < 0.05). In the AH, the amplitude was 49% at 1 h after initial infusion of propofol, 102% at 2 h, 102% at 3 h, 92% at 4 h, 71% at 5 h, and 63% at 6 h. Compared to the 2-h time point, MEP decreased significantly by 10% at 4 h (P < 0.005), by 31% at 5 h (P < 0.0000005), and by 39% at 6 h (P < 0.05). Conclusions MEP amplitude significantly decreased in the upper limbs at 5 and 6 h and in the lower limbs at 4, 5, and 6 h after the initial infusion of propofol, respectively. The influence of anesthetic fade could influence false positive MEPs during long spinal surgeries.